1981
DOI: 10.1002/jmv.1890070204
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 37: Identification and characterization of a medically important new adenovirus type of subgroup D

Abstract: A new human adenovirus has been isolated from 62 eyes with (kerato)conjunctivitis and from nine genitourinary sites. The virus is closely related in haemagglutination inhibition tests to adenovirus type 19 (Ad 19) and Ad 10. Antiserum adsorption experiments demonstrated the presence of three haemagglutinin antigens in the virus: One unique, another common to Ad 19, and a third common to Ad 10 and 19. In neutralization tests, the virus is distantly related to Ad 13, 30, 19, and 10. Despite this relationship, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 11 publications
2
57
0
Order By: Relevance
“…Some cross-reaction with Ad-19 was observed. NT cross-reaction between Ad-37 and Ad-19 has been reported by previous workers (1,6 ).…”
Section: Discussionsupporting
confidence: 62%
“…Some cross-reaction with Ad-19 was observed. NT cross-reaction between Ad-37 and Ad-19 has been reported by previous workers (1,6 ).…”
Section: Discussionsupporting
confidence: 62%
“…The fiber consists of a tail, shaft, and knob domain (8). Trimerization of the fiber protein is noncovalent and dependent on ␤-sheet structures in the shaft, while the globular knob domain consists of an eight-to nine-stranded antiparallel ␤-sandwich connected by loops (9,34). Each of the eight or nine strands is named A to H or A to J, respectively, while the loops are referred to as AB, CD, EF, etc.…”
mentioning
confidence: 99%
“…However, species D serotypes 8,19, and 37 (causing epidemic keratoconjunctivitis) have been shown to bind sialic acid instead of CAR (1,3,9,11,17). Recently it has been suggested that Ad37 can also bind to CD46 (44).…”
mentioning
confidence: 99%
“…They are non-oncogenic and are capable of complete agglutination of rat cells. These viruses, especially type 19, have been described as causal agents of ophthalmic diseases, such as keratoconjunctivitis (Dawson et al, 1970;Desmyter et al, 1974;Hierholzer et al, 1974;Guyer et al, 1975;Darougar et al, 1977;Wadell & de Jong, 1980;de Jong et al, 1981 ;Keenlyside et al, 1983;Kemp et al, 1983). Their genomes contain about 58% GC and the homology between the DNAs of the subgenus D AVs is o/ 94 to 99/o.…”
Section: Introductionmentioning
confidence: 99%